2016
DOI: 10.1007/s11626-016-0010-8
|View full text |Cite
|
Sign up to set email alerts
|

Flavone inhibits migration through DLC1/RhoA pathway by decreasing ROS generation in breast cancer cells

Abstract: Tumor suppressor protein deleted in liver cancer 1 (DLC1) is a RhoGTPase-activating protein (RhoGAP) and inhibits cancer cell migration by inactivating downstream target protein RhoA. A few studies have reported the regulations of reactive oxygen species (ROS) on RhoGAP. In this study, we investigated flavone (the core structure of flavonoids)-induced regulation on ROS generation and DLC1/RhoA pathway in MCF-7 and MDA-MB-231 breast cancer cells and explored whether flavone-induced upregulation of DLC1 is media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Flavonoid could protect human sperm against the damaging effects of FeSO 4 /H 2 O 2 (Huang et al 2014). Recently, it has been found that flavone works against cancer growth by direct targeting (Ganai 2017;Sajjadi et al 2018;Wang et al 2018b), and inhibits migration through DLC1/RhoA pathway by decreasing ROS generation in cancer cells (Zhu et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoid could protect human sperm against the damaging effects of FeSO 4 /H 2 O 2 (Huang et al 2014). Recently, it has been found that flavone works against cancer growth by direct targeting (Ganai 2017;Sajjadi et al 2018;Wang et al 2018b), and inhibits migration through DLC1/RhoA pathway by decreasing ROS generation in cancer cells (Zhu et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the results of our study are consistent with those of previously published ndings, in that they suggest that RET/PTC subfamily proteins from the TRIM superfamily are likely to have oncogenic roles in cancer. TRIM27 expression is a known modi er of apoptosis and disease progression in various cancers, such as lung, ovarian, colon, and esophageal cancer [5,7,27,28]. Indeed, TRIM27 has been shown to promote tumor invasion and growth in colon cancer through its promotion of the epithelial-mesenchymal transition and activation of the AKT pathway [5].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, TRIM27 has been shown to promote tumor invasion and growth in colon cancer through its promotion of the epithelial-mesenchymal transition and activation of the AKT pathway [5]. Similarly, the TRIM27 transcript level was found to be correlated with ovarian cancer metastasis, and it has been shown that TRIM27 knockdown induces cell cycle arrest by activating the p38 pathway [28]. Unlike other cancer types, the exact molecular mechanisms underlying the oncogenic action of TRIM proteins in RCC remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Besides cell proliferation and colony formation, the re‐expression of DLC1 also significantly inhibits cell migration and invasion through RhoA pathway in multiple myeloma cells (Ullmannova‐Benson et al, ), NPC cells (Feng et al, ), breast cancer cells (Zhu et al, ) and HCC (Yam et al, ). In the process of DLC1 regulating migration, DLC1 depends on Rho effector protein Dia1 but it needs no Rho kinase activity (Holeiter et al, ).…”
Section: The Function and Signal Pathways Dlc1 Involvesmentioning
confidence: 99%
“…The annual fish Nothobranchius guentheri are chosen as a vertebrate model for analysis of age‐dependent spontaneous tumorigenesis in our laboratory and we find that with SIRT1 upregulation, resveratrol induces apoptosis by deacetylating and dephosphorylating FoxOs, upregulating the interaction between DLC1 and SIRT1, as well as dephosphorylating DLC1, in spontaneous liver tumors. Resveratrol reduces senescence‐associated secretory phenotype by upregulating SIRT1 and downregulating NF‐κB, as well as increasing the interaction between SIRT1 and NF‐κB in the gut of annual fish (Chai et al, ; Ji et al, ; Liu et al, ; Liu et al, ; Zhu et al, ).…”
Section: Effects Of Natural Products and Drugs On Dlc1mentioning
confidence: 99%